Wet cupping for hypertension: a systematic review and meta-analysis. (4th July 2019) - Lu, Shuting; Du, Shizheng; Fish, Anne; Tang, Cong; Lou, Qingqing; Zhang, Xuefang
ABSTRACT: To assess the efficacy and safety of wet cupping in adults with hypertension, we conducted a systematic review and meta-analysis using 13 databases. Wet cupping alone or in combination with antihypertensive medication or acupuncture was used. Seven randomized trials were included, most not of high methodological quality. A few small studies suggested that wet cupping alone versus antihypertensive medication significantly reduced blood pressure and Traditional Chinese Medicine syndrome (hypertension-related symptoms). However based on current evidence, no firm conclusions can be drawn and no clinical recommendations made. Research projects included need validation. Studies indicate that wet cupping is a safe therapy.